Gambaran Efikasi Diri dalam Pengelolaan Hipertensi pada Lansia di UPTD Puskesmas Baturetno 1 Wonogiri - Arini Nurhidayati; Eska Dwi Prajayanti (Pusat Riset dan Inovasi Nasional, 2024)
Elderly is someone who has reached the age of >60 years. The elderly will experience a gradual physical, mental and social decline. The aging process in the elderly is characterised by degenerative changes making them vulnerable to a disease, one of which is hypertension. Hypertension is a cardiovascular disease characterised by a blood pressure condition of 140/90 mmHg. The management of hypertension in the elderly is carried out pharmacologically and non-pharmacologically, this is influenced by high or low self-efficacy. Self-efficacy is a person's belief in the ability to take action in accordance with the goals to be achieved. Knowing the description of self-efficacy in managing hypertension in the elderly at UPTD Puskesmas Baturetno I Wonogiri. This type of research uses descriptive methods with a quantitative approach. The sampling method is simple random sampling with inclusion criteria (respondents who have blood pressure> 140/90 mmHg, and the elderly> 60 years), exclusion criteria are respondents who are not present on the spot. The instrument used was the GSES (General Self-Efficacy Scale) questionnaire. The results of this study were 53 respondents (72.6%) elderly people with hypertension had high self-efficacy, while 20 respondents (27.4%) had low self-efficacy. From this study the majority of elderly people with hypertension at UPTD Puskesmas Baturetno I Wonogiri have high self-efficacy in managing their hypertension.